A Importância de eventos científicos no ambiente acadêmico - SILVA, Livia Barros da; CONCEIÇÃO, Suzanne Cardoso de Lima (137, 2023)
O presente trabalho apresentará a importância e o impacto da realização de eventos científicos para a comunidade acadêmica. A proposta é enfatizar o impacto positivo proporcionado com a realização desses eventos, com base nos resultados obtidos através da coleta de dados identificou-se a carência de eventos nas unidades da FATEC, é de suma importância o incentivo e a criação de mais eventos que integrem os cursos disponibilizados nas unidades. A fim de proporcionar a prática do conhecimento adquirido ao longo do curso, com temas relevantes como Marketing oferecendo oficinas, palestras e debates.

The objecttive of this work is to discuss the importance of scientific events in the academic environment. this final paper in addition to providing one methodology quantitative Among students and alumni of different campus the FATEC. was basead on Networking collection between students the academic community. This study exposes on the benefits provided to participants through the events as the initiation of new opportunities. Through lectures, debates and content presented in the execution of the events. The results of the research presents that 99% the studiens confirm the need for more events and demonstrate the gap that exists on your campus the campus. focusing on the interaction and exchange between different courses, where that there can be greater exchange and greater amplication of knowledge. To provide the practice of the knowledge acquired throughout the course, Through and workshops relevant.
The importance of scientific events in the academic environment
Keywords: Eventos; Educação; Comunicação; Gestão e Negócios